Rydberg atom-based sensors for radio-frequency electric field metrology, sensing, and communications. (December 2021) - Simons, Matthew T.; Artusio-Glimpse, Alexandra B.; Robinson, Amy K.; Prajapati, Nikunjkumar; Holloway, Christopher L.
Abstract: The recent redefinition of the SI bolsters the push towards quantum-based sensors. Rydberg atoms provide a natural link between atomic quantities and electromagnetic fields, where direct absolute measurements can be challenging. We review recent demonstrations of SI-traceable electric field metrology for both high frequency and static fields, communications reception, and angle-of-arrival detection using Rydberg atom spectroscopy.